Diagnosis of Electricity Distribution Network Disturbances Using Fault Tree Analysis - Ramli Mahaddin Hutajulu; Dino Erivianto; Muhammad Erpandi Dalimunthe (INFOKUM, 2025)
Disruptions in the electricity distribution network are one of the main problems that can reduce the reliability of electricity supply to customers. PT PLN ULP Balige as a customer service unit has the responsibility to ensure the continuity and quality of electricity distribution services in its operational area. This study aims to analyze the main causes of electricity distribution network disruptions using the Fault Tree Analysis (FTA) method. This method is used to identify the root causes of disruptions with a deductive approach arranged in the form of a fault tree. The data used in this study were obtained from disruption reports over the past year that occurred in the medium and low voltage distribution network at PT PLN ULP Balige. The results of the analysis indicate that several dominant factors causing disruptions include equipment component damage (such as transformers and cables), weather disturbances, and other external factors. With FTA modeling, logical relationships between causes can be systematically mapped, thereby facilitating the evaluation process and technical decision-making. This study is expected to be a basis for PT PLN ULP Balige in formulating prevention strategies and improving the reliability of the electricity distribution system through a more structured analytical approach.